Treatment of postmenopausal osteoporosis in women: a systematic review Tratamento da osteoporose em mulheres na pós-menopausa: uma revisão sistemática - Cristina Mariano Ruas Brandão; Marina Guimarães Lima; Anderson Lourenço da Silva; Graziele Dias Silva; Augusto Afonso Guerra Jr; Francisco de Assis Acúrcio (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Osteoporosis, a typical disease of the elderly, has become a frequent and relevant public health problem. Several drugs are available for treatment of osteoporosis, some of which are currently dispensed by the Brazilian Unified National Health System. The objective of this study was to present a systematic review of drugs for treatment of osteoporosis, focusing on the adequacy of clinical protocols based on existing evidence in the scientific literature. We conducted a search for randomized clinical trials in PubMed and LILACS that presented results for bone mineral density, incidence of vertebral fractures, and adverse effects. 32 articles met the review's inclusion criteria. Bisphosphonates were reported to have consistently reduced the risk of vertebral fractures. Hormone replacement therapy showed positive outcomes, but its use has been found to increase the risk of cardiovascular disease and breast cancer. Teriparatide and monofluorophosphate also showed efficacy against osteoporosis. Calcium and vitamin D were given to patients as food supplements. A osteoporose, doença típica dos idosos, vem se tornando um dos problemas mais freqüentes e relevantes no âmbito da saúde pública. Vários medicamentos estão disponíveis para o seu tratamento, alguns disponibilizados pelo SUS. Este estudo apresenta uma revisão sistemática dos medicamentos destinados ao tratamento da osteoporose, buscando subsidiar as discussões a respeito dos protocolos clínicos, com base em evidências científicas na literatura. Foi realizada busca de ensaios clínicos randomizados na base de dados PubMed e LILACS que apresentavam resultados de densidade mineral óssea, incidência de fraturas vertebrais e reações adversas aos medicamentos. Nos 32 artigos revisados, a classe de medicamentos bifosfonados foi a mais freqüente e a que melhor tem demonstrado sua eficácia clínica, principalmente o alendronato e o ibandronato via endovenosa. A terapia de reposição hormonal demonstrou efeito, mas seu uso tem sido associado ao aumento de risco de doenças cardiovasculares e outras. Teriparatida e monofluorfosfato apresentaram eficácia antiosteoporótica. Cálcio e vitamina D foram dados aos pacientes como suplemento alimentar.